Educação ambiental e os resíduos sólidos em área rural: um estudo de caso de uma escola do campo em Guaíra-PR - Rodrigues, Fernando Alvacir (2017)
It is known that waste discarded in a wrong way causes negative impacts, and it is extremely important to have conscious habits of care and protection with regard to the environment. There fore our research had the objective of investigating EA practices and the impact of the absence of solid waste collection in the rural area of the high school community located in the District of Dr. Oliveira Castro, located in the municipality of Guaíra - Paraná. In this way, we sought to identify with the community initiatives and perceptions about the environmental management of solid waste, based on sustainable practices guided by an ecologically healthy environment and balanced as a right to life. Environmental management of solid waste has as its guiding principles the national environmental policy (1981), the national solid waste policy (2010) and the curricular guidelines of environmental education (2012). The research is configured as a qualitative and descriptive case study, with the application of a semi-structured questionnaire, to 30 (thirty) high school students, 3 (three) teachers, 10 (ten) rural residents and the managers of the Secretary Municipal Environment and Agriculture, State of the Alderman Camp Samuel Benck, on the application of resolution no. 2, of June 15, 2012, which establishes the national curricular guidelines for environmental education, on the dissemination of environmental issues in the school community through lectures, workshops, and production of recyclables of solid waste can cause, this work comes With the proposal to alert and sensitize the community of the extreme relevance of environmental education, aiming at the healthy living of the human being on our planet. It is concluded that this research raised data on the actions and practices experienced by the target audience, about the school's political pedagogical project, highlighting the importance of working with Environmental Education (EA) and the correct allocation of solid waste.